2019
DOI: 10.1371/journal.pone.0219424
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist counseling in early pregnancy—Results from the SafeStart feasibility study

Abstract: Background Community pharmacists are available to counsel women in early pregnancy, but no studies have assessed the feasibility of such a service. Objective To test the feasibility of a pharmacist consultation in early pregnancy and to inform the design of a definitive trial. Setting Six community pharmacies in Norway from Oct. to Dec. 2017. Method We evaluated recruitment approaches and an automatic data preproce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…The CP service may not be implementable in nonintegrated outpatient practices, obstetric offices, or in a community pharmacy. While the SafeStart feasibility study in Norway found that it was feasible to provide community pharmacist consultations in early pregnancy, 22 our results may not be generalizable to community pharmacists in the United States.…”
Section: Limitationscontrasting
confidence: 69%
See 1 more Smart Citation
“…The CP service may not be implementable in nonintegrated outpatient practices, obstetric offices, or in a community pharmacy. While the SafeStart feasibility study in Norway found that it was feasible to provide community pharmacist consultations in early pregnancy, 22 our results may not be generalizable to community pharmacists in the United States.…”
Section: Limitationscontrasting
confidence: 69%
“…consultation with a pharmacist was most useful when tailored to their needs and would recommend the consultation to other pregnant women. 22 The majority of the literature on prenatal care by pharmacists has focused on the pharmacist's role in medication management and education for pregnant women. 5,6,9,13,[23][24][25] Little has been reported on the value that pregnant women place on pharmacists or other health care practitioners who provide information on medication use before or during pregnancy.…”
Section: Connectedness To the Health Care Teammentioning
confidence: 99%
“…Every other participant enrolled in the study was allocated to the intervention group. The ADPS has been described previously [13].…”
Section: Study Design and Sample Sizementioning
confidence: 99%
“…The study pharmacists received a study manual describing each part, with examples of relevant wording and questions. A consultation guide has previously been published [13]. In short, the introduction focused on getting to know the participant and setting the parameters for the consultation (content and time).…”
Section: Performing the Consultationmentioning
confidence: 99%
See 1 more Smart Citation